2018
DOI: 10.26832/24566632.2018.030409
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of two strawberry (Fragaria ananassa Duch.) cultivars of Bangladesh

Abstract: Bangladesh during the period of February to November, 2015. In the experiment, runners of two strawberry cultivars viz. BARI Strawberry -1 and Modern Strawberry-5 (Festival) were cultured on MS media supplemented with different concentrations of BAP (1.0, 1.5 and 2.0 mgL -1 ) and Kin (0.1, 0.5 and 1.0 mgL -1 ) for multiple shoot regeneration. The experiment was laid out in Completely Randomized Design (CRD) with three replications. The highest number of shoots (10.41) was obtained from Modern Strawberry-5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the present experiment, it was noticed that percentage of shoot formation was low in all the combinations of BAP and Kn compared to . Previously shoot formation by using different concentration and combinations of BAP and Kn from runner tips (Roy et al 2018), nodes (Sakila et al 2007) and leaf explants (Zakaria et al 2014) were reported. Shoots were induced in clusters (Fig 1f), and were transferred to three different media for elongation.…”
Section: Sterilants and Their Combinationmentioning
confidence: 99%
“…In the present experiment, it was noticed that percentage of shoot formation was low in all the combinations of BAP and Kn compared to . Previously shoot formation by using different concentration and combinations of BAP and Kn from runner tips (Roy et al 2018), nodes (Sakila et al 2007) and leaf explants (Zakaria et al 2014) were reported. Shoots were induced in clusters (Fig 1f), and were transferred to three different media for elongation.…”
Section: Sterilants and Their Combinationmentioning
confidence: 99%